Gradients of thalamic connectivity in the macaque lateral prefrontal cortex - Borra, Elena; Rizzo, Marianna; Luppino, Giuseppe (Frontiers in Integrative Neuroscience, 2023)
In the primate brain, the lateral prefrontal cortex (LPF) is a large, heterogeneous region critically involved in the cognitive control of behavior, consisting of several connectionally and functionally distinct areas. Studies in macaques provided evidence for distinctive patterns of cortical connectivity between architectonic areas located at different dorsoventral levels and for rostrocaudal gradients of parietal and frontal connections in the three main architectonic LPF areas: 46d, 46v, and 12r. In the present study, based on tracer injections placed at different dorsoventral and rostrocaudal cortical levels, we have examined the thalamic projections to the LPF to examine to what extent fine-grained connectional gradients of cortical connectivity are reflected in the topography of thalamo-LPF projections. The results showed mapping onto the nucleus medialis dorsalis (MD), by far the major source of thalamic input to the LPF, of rostral-to-caudal LPF zones, in which MD zones projecting to more caudal LPF sectors are located more rostral than those projecting to intermediate LPF sectors. Furthermore, the MD zones projecting to the rostral LPF sectors tended to be much more extensive in the rostrocaudal direction. One rostrolateral MD sector appeared to be a common source of projections to caudal prefrontal areas involved in the oculomotor frontal domain, a more caudal and ventral MD sector to a large extent of the ventral LPF, and middle and dorsal MD sectors to most of the dorsal LPF. Additional topographically organized projections to LPF areas originated from the nucleus pulvinaris medialis and projections from the nucleus anterior medialis selectively targeted more rostral sectors of LPF. Thus, the present data suggest that the topography of the MD-LPF projections does not adhere to simple topological rules, but is mainly organized according to functional criteria.